Response of Shoots from Porang Leaf Bulbs to Cytokinins and IAA in Shoot Multiplication In Vitro - Erfa, Lisa; Maulida, Desi; Hamiranti, Rahmadyah; Ferziana, Ferziana; Yuriansyah, Yuriansyah; Safitri, Betari; Yeni, Yeni (International Journal of Applied Sciences and Smart Technologies, 2024)
The growth regulators in media have the potential to significantly influence the process of in vitro plant regeneration. The response of explants in forming shoots also depends on the type and the combination of growth regulators. This research aimed to identify the most optimal type and concentration of cytokinin for the multiplication of in vitro porang shoots. Additionally, it determined whether the addition of cytokinins should be accompanied by auxin/IAA for porang shoot multiplication. To achieve these objectives, a completely randomized design with six replications was employed, followed by a 5% BNJ. The tested treatments consisted of various combinations of growth regulators. Several observations were recorded, including the speed of explants forming prospective shoots/shoots (days), the age of the explants forming prospective shoots/shoots, the number of prospective shoots and shoots produced per explant, and shoot height (cm). The results showed that 1) Tdz 2 and IAA 0.5 mg.l-1 formed the highest shoots candidates and shoots in porang multiplication in vitro, and 2) the addition of BAP and Tdz 2 mg.l-1 should be combined with IAA 0.5 mg.l-1, while BAP and Tdz 3 mg.l-1 did not require IAA.